EPIDEMIOLOGICAL PROFILE OF MEN WITH PROSTATE CANCER ATTENDED IN A TEACHING HOSPITAL - Marina Viana Fernandes; Júlia Trevisan Martins, Alexandrina Aparecida Maciel Cardelli; Sonia Silva Marcon; Renata Perfeito Ribeiro (Universidade Federal do Paraná, 2014)
This epidemiological, descriptive, cross-sectional research aimed to outline the epidemiological profile of men with prostate cancer assisted in a Teaching Hospital in the south of Brazil. The data were collected through interviews with 54 men, using a structured questionnaire addressing socio-demographic characteristics, health behavior and history of the disease. The SPSS Program, version 19, was used for analysis of the data. The results indicated a mean age of 74.8 years old; the prevalence of Caucasians; low educational level; retirees and living with family members. Behaviors of risk for prostate cancer were identified: poor food; smoking; alcoholic drinks; and a mean time taken to seek treatment of over 30 days. Public managers and the multi-professional team must adopt strategies in order to inform men about the importance of a positive preventive attitude.